Reflections on the identification of pain in patients unable to communicate verbally - Bernardini, Patrícia Dal Bem; Montezeli, Juliana Helena; Sade, Priscila Meyenberg Cunha (Revista de Enfermagem UFPE on line, 2012)
ABSTRACT Objective: to reflect on the recognition of physiological manifestations of pain in patients unable to communicate verbally and its interfaces with the nursing assistance to the patient in critical condition. Method: this is a reflective study based on literature review which consists of the phases for determining the goal, preparing the work plan, identifying the sources, finding the sources, obtaining the material, reading the material, taking of notes, making of cards, and writing the paper. Results: besides the technical aspects, nursing is characterized by the aesthetic expression, as it is also an art. Thus, the subjective signs which should be considered in the care to the incommunicable patient emerge, including the pain assessment. The physiological manifestations and pain assessment are approached, as well as the pain frames in the patient without possibility of verbal communication and the importance of indentifying pain for providing the nursing assistance to the critical patient. Conclusion: to recognize the physiological manifestations of pain and its particularities in the critical patient unable to communicate is crucial for a comprehensive nursing assistance, which goes beyond the mechanistic basis of the profession resulting from the biomedical model. Descriptors: nursing assistance; pain assessment; critical care. RESUMO Objetivo: refletir sobre o reconhecimento das manifestações fisiológicas da dor em pacientes incapazes de se comunicar verbalmente e suas interfaces com a assistência de enfermagem ao paciente em estado crítico. Método: trata-se de estudo reflexivo baseado em revisão de literatura composta das fases de determinação do objetivo, elaboração do plano de trabalho, identificação das fontes, localização das fontes, obtenção do material, leitura do material, tomada de apontamentos, confecção de fichas e redação do artigo. Resultados: além dos aspectos técnicos, a enfermagem caracteriza-se pela expressão estética, uma vez que também é uma arte. Assim, emergem os sinais subjetivos que devem ser considerados no cuidado ao paciente incomunicável, entre eles a avaliação da dor. Discorre-se sobre as manifestações fisiológicas e mensuração da dor, as especificidades dos quadros álgicos no paciente sem possibilidade de comunicação verbal e sobre a importância da identificação da dor para prover a assistência de enfermagem ao paciente crítico. Conclusão: reconhecer as manifestações fisiológicas da dor e suas especificidades no paciente crítico impossibilitado de comunicar-se é fundamental para uma assistência de enfermagem abrangente, que extrapole as bases mecanicistas da profissão advindas do modelo biomédico. Descritores: assistência de enfermagem; avaliação da dor; cuidados críticos. RESUMEN Objetivo: reflexionar acerca del reconocimiento de las manifestaciones fisiológicas del dolor en pacientes incapazes de comunicarse verbalmente y sus interfaces con la asistencia de enfermería al paciente en estado crítico. Método: esto es un estudio reflexivo basado en revisión de literatura compuesto de las fases de determinación del objetivo, elaboración del plan de trabajo, identificación de las fuentes, ubicación de las fuentes, obtención del material, lectura del material, tomada de notas, confección de fichas y redacción del artículo. Resultados: además de los aspectos técnicos, la enfermería se caracteriza por la expresión estética, ya que también es una arte. Así, emergen los señales subjetivos que deben ser considerados en la atención al paciente incomunicable, incluyendo la evaluación del dolor. Las manifestaciones fisiológicas y la mensuración del dolor son discutidas, así como las especificidades de los cuadros álgicos en el paciente sin posibilidad de comunicación verbal y la importancia de la identificación del dolor para ofrecer la asistencia de enfermería al paciente crítico. Conclusión: reconocer las manifestaciones fisiológicas del dolor y sus especificidades en el paciente crítico imposibilitado de comunicarse es esencial para una asistencia de enfermería abarcadora, que va más allá de las bases mecanicistas de la profesión advenidas del modelo biomédico. Descriptores: asistencia de enfermería; evaluación del dolor; cuidados críticos.